Assessing Safety Climate Dimensions in the Textile Industry: A Correlational Study Using the NOSACQ-50 Framework - Rici Riansyah; Tyas Lilia Wardani; Isna Qadrijati; Jihan Faradisha; Afrian Eskartya Harjono; Rizqy Kartika Sari; Rachmawati Prihantina Fauzi; Reni Wijayanti (Media Publikasi Cendekia Indonesia, 2026)
The manufacturing sector, particularly the textile industry, faces high occupational accident risks due to inadequate Occupational Health and Safety (OHS) culture. This study evaluates the safety climate in the textile industry and examines the relationship between the seven dimensions of the NOSACQ-50 framework and the overall safety climate. Utilizing a descriptive quantitative, cross-sectional approach, data was collected from 100 purposively sampled workers through the NOSACQ-50 questionnaire, direct workplace observations, and interviews. Data was analyzed using univariate and bivariate (Spearman's rank) methods. Univariate results indicated a